FINANCING OF LINEAR ROAD INFRASTRUCTURE IN POLAND - Stanisław Bereziński; Tomasz Rokicki (Polityki Europejskie, Finanse i Marketing)
The main purpose of the paper was to identify and present the situation and changes in the level of expenditure on public roads in Poland, taking into account the division of the country into voivodships. The data concerned the period from 2005 to 2017. Sources of materials were the analysis of available literature in the field of road transport, legal acts, data from the CSO database. The comparative method was used in the paper, dynamics indicators were evaluated, the Gini concentration coefficient was calculated and the degree of concentration was presented using the Lorenz curve. Pearson's linear correlation coefficients were also used. A descriptive, tabular and graphic method were used to present the results. Investment outlays on roads apply to both the construction of new roads and the repair of existing ones. Between 2005-2017, the length of public roads in Poland increased by 11% to 422,000 km. Changes in individual voivodships and in subsequent years varied. The largest increase in road length occurred in Podlaskie and Lublin, while the smallest was in Opole. The largest expenditure on public roads was incurred in 2009-2011, which was related to the preparation for the Euro 2012 football tournament, which took place in Poland and Ukraine. Investment outlays were related to the level of economic development of voivodships and the resources of public roads. The only exception to this rule occurred in 2009-2011, when many road investments were centrally financed by the government.